What Impacts Leisure Activity and Diet among Immigrants? Mexican Immigrants' Leisure Participation and Food Patterns in the Midwestern U.S. (27th August 2021) - Phan, Maggie M.; Stodolska, Monika
Abstract: High obesity rates and increasing prevalence of chronic diseases among Latinos make preservation of healthy traditional dietary practices an important public health issue in the United States. This study, conducted in the midwestern United States, evaluated factors impacting food practices, dietary patterns, and leisure among Mexican immigrants. The results of the study, which was based on semi-structured interviews with 23 Mexican immigrants, indicated such factors included elements of the new environment, cultural beliefs regarding food and diet, psychological factors and taste preferences, and changes in lifestyles and daily schedules. These findings highlight the importance of bringing the sense of leisure back to food preparation and food consumption, which becomes critical when immigrants are faced with the task of cooking with only ingredients available in their region of the United States. Individuals will then be less likely to rely on consuming local convenience foods commonly high in fat, sugar, and salt.